A responsabilidade profissional em Educação Física Escolar : o ponto de vista dos professores - Nascimento, Glauce Yara do (2010)
The changing economic, social and cultural rights in recent decades have required a number of individuals increasing knowledge, skills and commitment to the professional activities they perform. These changes come in the form of teaching and administrative reform curricula, with an ultimate aim of preparing students to face these changes. However, reforms are not effective if the agents of education (teachers and staff, operational and administrative) are not aware of their responsibilities and work commitments. In this context the figure of the professional teacher education has gained more prominence, since it is one of the most important agents in achieving educational goals. Therefore, this study aimed to understand how the physical education teachers describes and interprets theirs professional responsibilities. The research method used was qualitative-descriptive, with the use of two different techniques for collecting information: a questionnaire with open and closed, and the focus group, in which eight physical education teachers with experience in basic education is met to discuss issues related to professional liability. From the Content Analysis, we found that the teachers feel responsible for a series of activities and professional circumstances that permeate his work, among them are: a) effective learning of students; b) developing a creative teaching, autonomous and reflective; c) responsibility for the physical, mental and emotional development of learners; d) keep your workspace organized and clean; e) develop strategies for learning and encouraging diverse; f) to safeguard the image and status of the profession, and g) worry with the continuing professional development. Considering the above, we realize that the responsibilities of teachers of physical education in school are many and include various areas: administrative, pedagogical, curricular, social and professional. We realized that the initial training is one of the most relevant factors that may help in understanding the size range for professional liability, but nevertheless the model of professional preparation courses are not effective in this regard. We also note that there is a difficulty in understanding and characterization of the responsibilities of teachers, first, as is common in higher specific activities be confused with a much larger responsibility that each subject behaves as it is the task of the whole society and not exclusive school, caring for the human and cultural formation of youth and children. However, we found that teachers care about the quality of your professional performance, as they plan their classes, discuss the content and seek alternatives to address the problems of professional practice, which also shows a commitment to career. However, despite all the efforts we can not guarantee that this is a commitment shared by all physical education teachers who work in school.